Rural women‘s knowledge of the preventive and therapeutic role of food in Kafr El - Sheikh governorate, Egypt - Barakat, Amera Barakat; Abdullah, Ahmed Mustafa; Hassan, Noha Ezzahi (Arab Journal for Sciences and Research Publishing, 2016)
This research was mainly aimed at studying rural women's knowledge of the preventive and therapeutic role of food in Kafr Al-Sheikh governorate. To achieve the goal of the study, Kafr Al-Sheikh governorate was chosen as an area for this study, and a center was chosen from among the centers of the province randomly, resulting in the random selection of riyadh center, followed by the selection of a random village among the villages of the center, resulting in the random selection of the village of Abu Mustafa, and was determined The study of all the 1,307 rural wives in Abu Mustafa village (based on the total number of families) in this village of 1,307 families, of whom a random sample of 304 were selected, and the data were completed from the rural women surveyed. 100% using the interview questionnaire. Percentages, arithmetic mean, standard deviation, simple correlation coefficient, multiple correlation, and step-wise were used to identify the most independent variables with a moral effect that contribute to the interpretation of variability in the dependent  variable. The statistical analysis was done using SPSS,V16. The most important results for the rural knowledge of the sample were: that about 97% of the respondents were in the middle and low knowledge category with regard to the preventive and therapeutic role of food, and that about 99% of the respondents were in the middle and low-income categories of medical benefits of medicinal plants. And aromatic, and that about 64% of the sample fell in the category of not knowing the foods that protect us from diseases, and that about 28% of the sample who have knowledge of this area are low level of knowledge, and that about 2.6% of the sample fell in the category of not knowing what is allowed and forbidden food for patients, and that About 54% of those with knowledge of the permitted and forbidden food for patients for diseases studied have low knowledge, as the results showed a direct and moral correlation at the probability level 0.01 between rural women's knowledge of the preventive and therapeutic role of food and independent variables. The age of research, the educational status of the research, the education of the research family, the condition of the dwelling, the possession of household items, the openness of civilization and culture, participation in development projects in the village, sources of food information, and self-appreciation to lead the opinion of the researched in the field Food, total monthly household income in pounds, total monthly food expenditure, multiple roles of research, the emergence of research, and living facilities, while the results showed a moral correlation in reverse at the probability level 0.01 among the independent variables of: Responsible for determining the components of food, possession of agricultural land, captive cohesion, and the independent variables included in the study combined are linked to the knowledge of rural women researched in the preventive and therapeutic role of food with a multiple correlation factor of 0.754, and the morality of that relationship has been proven at the level Probability 0.01, based on the calculated value of "P") at 23.703, and the results indicate that the combined independent variables explain 56.9% of the total variation in the dependent variable based on the value (R2).
Keywords: healthy food; correct nutrition; correct eating habits; the preventive and curative role of food